2017
DOI: 10.1111/jocd.12443
|View full text |Cite
|
Sign up to set email alerts
|

Bimatoprost ophthalmic solution in facial vitiligo

Abstract: Bimatoprost seems to be promising in treating stable vitiligo but large-scale studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…18 Another study by Jha et al assessed the efficacy of 0.03% bimatoprost in treating stable facial vitiligo lesions. 10 This showed that half of the patients had more than 50% repigmentation by week 12. The results of this study supported the idea that the treatment on facial lesions offered the best response.…”
Section: P Valuementioning
confidence: 95%
See 2 more Smart Citations
“…18 Another study by Jha et al assessed the efficacy of 0.03% bimatoprost in treating stable facial vitiligo lesions. 10 This showed that half of the patients had more than 50% repigmentation by week 12. The results of this study supported the idea that the treatment on facial lesions offered the best response.…”
Section: P Valuementioning
confidence: 95%
“…Previous clinical study by Grim et al was conducted in nonfacial vitiligo using 0.03% of bimatoprost solution, and no patients achieved greater than 50% repigmentation 18. Another study by Jha et al assessed the efficacy of 0.03% bimatoprost in treating stable facial vitiligo lesions 10. This showed that half of the patients had more than 50% repigmentation by week 12.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of iris and periocular skin hyperpigmentation in patients with glaucoma led to its use in vitiligo (55). This hyperpigmentation seems to be due to an increase in melanogenesis (56).…”
Section: Methotrexate (Mtx)mentioning
confidence: 99%
“…Indeed, this analysis, correlated with other parameters such as onset age and associated diseases, may help the researchers to define and categorize the different variants of vitiligo, since a rigorous clinical classification is still missing [ 3 , 4 , 5 ]. Also, the patches detection and area measurement can help assessing the treatment effectiveness [ 6 , 7 ]. To this purpose, recent studies demonstrated that black light (around 365 nm [ 8 ]) is crucial in highlighting vitiligo patches, enhancing the contrast with respect to healthy skin [ 9 ].…”
Section: Introductionmentioning
confidence: 99%